Anomalous systemic arterial supply to the left basal lung with a calcified abnormal vessel: a case report - Motoki Ebihara; Sakashi Fujimori; Souichiro Suzuki; Takuma Yotsumoto; Shinichiro Kikunaga; Reo Ohtsuka; Shigefumi Matsuyama (Surgical Case Reports)
Abstract Background Anomalous systemic arterial supply to the normal basal segment of the left lower lobe is a congenital abnormality of the lung, frequently and is generally diagnosed at a young age. Surgery is generally recommended if symptoms such as blood sputum or fever are observed. Resection of the abnormal artery is often performed at an early age, with only few reports of surgery being performed at an older age. In addition, to the best of our knowledge, there are no reports on surgical treatment of abnormal calcified vessels to date. Herein, we have presented a case in which a calcified aberrant vessel of lung was resolved surgically. Case presentation A 65-year-old female, previously diagnosed with anomalous systemic arterial supply to the left normal basal segment of the left lung lower lobe of lung was under observation on the basis of being asymptomatic. The patient presented to the emergency room with the chief complaint of blood in the sputum and she was referred to our hospital for a surgery. Computed tomography showed circumferential calcification of the intima of the abnormal vessel, which might have contributed to incomplete resection of the artery if automatic sutures were used. Thus, the abnormal vessel was ligated and dissected using pledgeted 4–0 polypropylene sutures and vessel clips under open thoracotomy followed by left lower lobectomy. The patient was discharged seven days after surgery without any serious surgical complications. Conclusions Vascular congenital anomalies of the lung are often operated at a young age presenting due to the associated symptoms. However, even if the disease is discovered incidentally and does not cause any symptoms or calcification in the aberrant artery, early surgical intervention is important due to the possibility of calcification occuring in the future. This can help minimize the degree of surgical invasion.